2018
DOI: 10.3390/infrastructures3030018
|View full text |Cite
|
Sign up to set email alerts
|

Critical Analysis of International Precast Concrete Pipe Standards

Abstract: Reinforced concrete pipe (RCP) standard guidelines and industry practice have rather been disconnected from the end-users' expectations. No genuine effort has so far been made to create synergy between the expertise gained and advances made around the world. With the advent of strong competition from flexible pipe products and changing end-user expectations, a critical look at the current state-of-the-art is needed. In the present paper, RCP standards from a study area representing a quarter of the world's pop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 11 publications
2
4
0
Order By: Relevance
“…Results of the crushing tests including the load versus time associated with the cracks' width, and schematic strain profile at the end of the experiment of the three smart TRC pipes are given in figure 5 and summarized in table 3. The results yield the following observations: First, it is observed that generally the macro-structural responses of all three pipes are similar and follow a known response of concrete pipes [33,[37][38][39][40][41]. Four cracks were formed in each pipe.…”
Section: Crushing Test-evaluation Of the Design Statesupporting
confidence: 53%
“…Results of the crushing tests including the load versus time associated with the cracks' width, and schematic strain profile at the end of the experiment of the three smart TRC pipes are given in figure 5 and summarized in table 3. The results yield the following observations: First, it is observed that generally the macro-structural responses of all three pipes are similar and follow a known response of concrete pipes [33,[37][38][39][40][41]. Four cracks were formed in each pipe.…”
Section: Crushing Test-evaluation Of the Design Statesupporting
confidence: 53%
“…Accordingly, the ultimate load and D-load of the concrete pipe can be calculated, both of which are usually specified to describe the bearing capacity of concrete pipes [28]. The D-load is defined as the load required to result in a 0.01-inch (0.3 mm) crack in a pipe, and the ultimate load (referred to as the D u ) is the maximum load a pipe can bear before it fails [29].…”
Section: Characterization Approach Of the Bearing Capacity Of Sewer P...mentioning
confidence: 99%
“…Since the '50 s of the twentieth century, significant enhancement has been made in this field as many new materials have been introduced. Nowadays, modern gravity sewer systems are made of polyvinyl chloride (PVC), corrugated steel (CSP), high-density polyethylene (HDPE), polypropylene (PP), fiberglass, steel-reinforced high-density polyethylene (SRHDPE), or metal pipes (Wong and Nehdi 2018). However, all of these materials are exposed to microbial activity and biofilm formation.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it is also non-flammable and resistant to rusting, tearing, buckling, or deflection. On the other hand, the long-term durability of modern plastic materials has not yet been confirmed because these materials were developed in recent decades and still are being tested (Wong and Nehdi 2018). However, the long operating time of concrete sewer systems exposes them to biogenic corrosion.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation